Evaluating the Realization Rate of Objectives of Rural Pivot Plans in Iran: a Case Study of Ghale Kohane Village in Saghes City, Iran - Farajollahi, Akbar; Arzjani, Zahra; Tajfar, Reza (International Journal of Bio-resource and Stress Management, 2012)
Rural pivot plans are meant to improve the facilities in villages. Restoration and revitalization are pivot dimensions of pivot plans including social, cultural and economic aspects. Final goal includes reconstructing rural areas to deliver welfare services and medical and industrial facilities. The aim of this study was finding and understanding how to implement plan and its impact on the rural, social and economic aspects of Ghale Kohane village. This study was completed by descriptive-applied method using field observation and questionnaire. Sixty households were selected from Ghale Kohane village according to the Kutcheran formula. Data were analyzed using inferential statistics. Qualitative data were converted into quantitative data using excel software and analyzed by SPSS software. Results indicated that pivot plan in Ghale Kohane village affected economic, social and structural aspect of this village such as job opportunity, income increase, immigration decrease, increasing awareness of people, promoting participation rate, developing pavement, improving quality of sewage system, and promoting housing situation for villagers